The Systematic Review on Green Finance in the Banking Industry: Perspectives from a Developing Country - Mujuka, Edward; Sporta, Fred (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This paper systematically views the literature on the Green Finance (GF) gap, which refers to the mismatch between the demand for and availability of GF in the banking industry of developing countries. GF is vital for supporting the transition to a sustainable economy. Still, it faces several challenges, such as a lack of standardized definitions, data, incentives, regulations, awareness, capacity, and access to finance. The paper uses a mixed-methods approach, combining bibliometric analysis and qualitative synthesis, to identify and analyze influential publications on the GF gap and synthesize the main findings and implications. The paper also provides potential solutions and recommendations to address the GF gap and suggests directions for future research in this field.